One-step preparation of hydrogenated ZrO2 microspheres by cathode plasma electrolysis. (27th July 2017) - Liu, Chenxu; Xiang, Qingyun; Yang, Mu; Wang, Shengdian; Wang, Linxiu; Zhang, Jin; He, Yedong
Abstract: Hydrogenated ZrO2 microspheres were directly prepared by cathode plasma electrolysis (CPE) in an aqueous solution of Zr(NO3 )4 5H2 O. Owing to the energy of plasma and the cathodic hydrogen evolution reactions, the CPE method combined the preparation of ZrO2 ceramic and the hydrogen treatment into only one step. The results showed regular microspheres consisting of tetragonal-ZrO2 and monoclinic-ZrO2 with 1–10 µ m in diameter were formed at relatively high concentration of Zr(NO3 )3 5H2 O. These ZrO2 microspheres contained about 52.54 µ g g −1 hydrogen which caused a narrow band gap (3.10 eV). Thus, the microspheres showed good photocatalytic activity under simulated sunlight, and the degradation of RhB dye reached nearly 58% for 3 h of irradiation, much better than the ZrO2 microspheres after dehydrogenation treatment.